Design and investigation of a high integrated reliable ceramic package for surface mount technology. (August 2021) - Tang, Lifeng; Wang, Yunyan; Liang, Qiushi; Xia, Qingshui; Zhou, Hao
Abstract: With the development of automobile, communication, computer, aerospace and artificial intelligence, Small Outline Packages (SOP) are difficult to meet the needs of putting more integrated circuits, analog-digital signal processing circuit, storage or multi-functional modules into one package, and letting them work on the same voltage for compacted space and high reliable application. Unlike conventional SOP packages, a ceramic package of CSOP64 with larger outline and bigger cavity is designed and fabricated for surface mount technology in this paper. Also fairly strict conditions of environmental reliabilities compared to criterions commonly used on accelerated testing, such as temperature cycling, thermal shock, mechanical shock, constant acceleration and gas leakage are carried out to assure the reliabilities of package. Coffin-Manson model, dual capillary model, finite element simulation and theory calculation methods are applied to explain the mechanism of reliability problems in this investigation. Experiment results showed that all samples passed tests. The reliability of fabricated package samples meet the requirement in application.